Strategi Mitigasi Kekerasan Seksual pada Santri: Studi Penerapan Religious Literacy (RL) di Pondok Pesantren Darul Faqih - Ikhsan, M. Alifudin; Khoirul Anam, Faris; Hanafi, Yusuf; Fauzi, Moh. Fery (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
This study aims to analyze the application of religious literacy as a strategy for mitigating sexual violence at the Darul Faqih Islamic boarding school. Sexual violence is a complex global issue with significant impacts on the physical, mental, and social health of victims. This phenomenon is also a serious concern in Indonesia, particularly in educational settings, including Islamic boarding schools. Involving 278 students from junior high school and senior high school levels, the program was implemented in two main phases: strengthening religious literacy through workshops that provided comprehensive understanding, and intensive mentoring and practical implementation, including counseling, developing policies for addressing sexual violence, and training practical skills for students and pesantren staff. The results of the program indicate that religious literacy integrated with a practical approach is effective in mitigating sexual violence within pesantren environments. This model not only enhances the individual capacities of students and educators but also contributes to institutional cultural change that supports a safe and gender-equitable educational environment. This initiative makes a significant contribution to the development of contextual and sustainable strategies for mitigating sexual violence in other Islamic educational institutions.